Sejarah dan perjalanan sila pertama pancasila dari era orde lama sampai era reformasi (SBY) - Arthur Aritonang (Davar : Jurnal Teologi, 2023)
AbstractThis article intends to trace the history of the sharp debate over the sound of the first Pancasila precepts among nationalists and political Islam. It is clear that this problem has not yet been resolved to be resolved, some Indonesians seem unable to come to terms with the sound of the first precepts. These efforts are still being fought for, either through political channels or through the birth of religious-based community organizations / mass organizations. In general, this effort is about to present the face of superiority in religion in Indonesia which in turn changes the way of being Indonesian religion from being intolerant of diversity. This indicates that Indonesian society seems to have started to ignore the meaning of the first Pancasila precepts. The purpose of this article is to trace the history of the first Pancasila precepts from the Old Order to the Reformation (SBY). Whether the way of religion in Indonesia shows the soul of the first Pancasila precepts or is it the other way around? The approach used in this article is a qualitative method that focuses on the literature on the first Pancasila precepts. The conclusion of this article is that the first Pancasila precepts experienced degradation until the end of the SBY administration. To overcome the problem of religious dissonance in Indonesia, Indonesian people need to live up to the values of the first Pancasila precepts. Key words: Pancasila First Principle, Islam, Politics, Religious Harmony. AbstrakArtikel ini hendak menelusuri sejarah perdebatan yang cukup tajam atas bunyi dari sila pertama pancasila di antara kalangan nasionalis dan islam politik. Persoalan ini nyata belum juga tuntas untuk diselesaikan sebagian masyarkat indonesia tampaknya belum dapat berdamai dengan bunyi dari sila pertama tersebut. Upaya tersebut masih terus diperjuangkan baik melalui jalur politik ataupun melalui lahirnya organisasi masyarakat/ormas yang berbasis agama. Usaha tersebut sebenarnya secara garis besar hendak menampilkan wajah superioritas dalam beragama di indonesia yang pada akhirnya mengubah cara beragama indonesia dari yang menjadi intoleran terhadap keberagaman. Hal ini mengindikasikan bahwa masyarakat indonesia seperti sudah mulai mengabaikan makna dari pancasila sila pertama. Tujuan dari artikel ini ialah menelusuri sejarah perjalanan pancasila sila pertama dari orde lama sampai reformasi (SBY). Apakah cara beragama di Indonesia memperlihatkan jiwa dari sila pertama pancasila ataukah malah sebaliknya?. Pendekatan yang digunakan dalam artikel ini ialah metode kualitatif yang menitikberatkan pada liteatur mengenai pancasila sila pertama. Kesimpulan dari artikel ini ialah pancasila sila pertama mengalami degradasi sampai masa berakhirnya pemerintahan SBY. Untuk mengatasi masalah ketidakrukunan umat beragama di Indonesia, masyarakat Indonesia perlu menghidupi nilai dari Pancasila sila pertama.Kata kunci: Pancasila Sila Pertama, Islam, Politik, Kerukunan Umat Beragama.